Effect of activated crumb rubber on the properties of crumb rubber‐modified bitumen. Issue 5 (6th February 2013) - Singh, B.; Kumar, Lokesh; Gupta, M.; Chauhan, Monika; Chauhan, G.S.
Abstract Bitumen modification was made with the activated crumb rubber concentrate and its efficacy was examined in terms of its consistency and rheological properties. It was found that softening point of the activated crumb rubber‐modified bitumen increased while its penetration and elastic recovery decreased compared with the nonactivated crumb rubber system. Based on contact angle results, the activated crumb rubber–bitumen system was found to be more wettable and exhibited better adhesion to the substrate than those of other systems. The shifting of glass transition temperature towards higher temperature and the occurrence of inter‐mix phases in the activated crumb rubber–bitumen system supported its superior temperature resistance. The difference in viscosity obtained between the activated and nonactivated crumb rubber systems is attributed to the high swelling of activated crumb rubber and its soluble fractions in the bitumen as viewed in scanning electron images. High complex modulus and low phase angle of the activated crumb rubber system over the entire range of temperatures indicated its reduced temperature susceptibility and more elasticity. The activated crumb rubber–bitumen system meets the requirements of commercial standard specification. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013